Consumption of Iron-Biofortified Beans Positively Affects Cognitive Performance in 18- to 27-Year-Old Rwandan Female College Students in an 18-Week Randomized Controlled Efficacy Trial - Murray-Kolb, Laura E.; Wenger, Michael J.; Scott, Samuel P.; Rhoten, Stephanie E.; Lung'aho, Mercy G.; Haas, Jere D. (Elsevier, 2017)
Background: Evidence shows that iron deficiency in adulthood may affect cognitive performance, possibly by disrupting neurotransmitter regulation or brain energy metabolism. Women of reproductive age (WRA) are among those who are most vulnerable to iron deficiency; however, they have been largely ignored in the literature relating iron status to cognition.